Langerhans Cells, T Cells, and B Cells in Oral Lichen Planus and Oral Leukoplakia - Amal Dafar; Angelica Siarov; Yasaman Mostaghimi; Jairo Robledo-Sierra; Shahin De Lara; Daniel Giglio; Göran Kjeller; Paulo Henrique Braz-Silva; Jenny Öhman; Bengt Hasséus (International Journal of Dentistry)
Although oral lichen planus (OLP) and oral leukoplakia (LPL) have different pathogenetic profiles, both may involve chronic inflammation. The aim of this observational study was to evaluate the inflammatory cell profiles of OLP and LPL. The inflammatory cell infiltrates in patients with OLP and LPL were analyzed for the presence of Langerhans cells (LCs; CD1a), T cells (CD3), and B cells (CD20), as well as for the proliferation marker Ki-67. Biopsied specimens from patients with OLP (N = 14) and LPL without dysplasia (N = 13) were immunohistochemically stained with antibodies directed against CD1a, CD3, CD20, and Ki-67, followed by quantitative analyses. A significant increase in the number of CD3+ cells and CD20+ cells was found in the submucosa of OLP, as compared to LPL (p<0.01). Likewise, the number of CD3+ cells was significantly higher in the epithelium of OLP than of LPL (p<0.05). No differences were found in the expression of Ki-67 and the number of CD1a+ cells between the two groups. Although an immune response is elicited in both conditions, there are differences at the cellular level between OLP and LPL. A more robust immune activation involving T cells and B cells is seen in OLP. The role of B cells in OLP needs to be further elucidated. Although the number of B cells in LPL is low, their role in the inflammatory response cannot be ruled out.